Emotional expression visual mismatch negativity in children. Issue 7 (6th September 2022) - Kovarski, Klara; Charpentier, Judith; Houy‐Durand, Emmanuelle; Batty, Magali; Gomot, Marie
Abstract: Detection of changes in facial emotions is crucial to communicate and to rapidly process threats in the environment. This function develops throughout childhood via modulations of the earliest brain responses, such as the P100 and the N170 recorded using electroencephalography. Automatic brain signatures can be measured through expression‐related visual mismatch negativity (vMMN), which reflects the processing of unattended changes. While increasing research has investigated vMMN processing in adults, few studies have been conducted on children. Here, a controlled paradigm previously validated was used to disentangle specific responses to emotional deviants (angry face) from that of neutral deviants. Latencies and amplitudes of P100 and N170 both decrease with age, confirming that sensory and face‐specific activity is not yet mature in school‐aged children. Automatic change detection‐related activity is present in children, with a similar vMMN pattern in response to both emotional and neutral deviant stimuli to what previously observed in adults. However, vMMN processing is delayed in children compared to adults and no emotion‐specific response is yet observed, suggesting nonmature automatic detection of salient emotional cues. To our knowledge, this is the first study investigating expression‐related vMMN in school‐aged children, and further investigations are needed to confirm these results.